2018
DOI: 10.17073/0368-0797-2018-6-470-477
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Vibrating Feeders-Screens for Mining and Metallurgical Industry

Abstract: The main scientific and practical results of the improvement of  vibrating feeders-screens for mining and metallurgical industry are  presented on the basis of dynamic calculation of the vibrating feederscreen with two differently directed self-balancing vibrators. Methods  of theoretical generalizations are described using mathematical statistics, physical and mathematical modeling, computation and feasibility studies, laboratory and full-scale experimental studies, industrial  tests in the conditions of oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Failure diagnosis requires accurate dynamic modeling and system identification [6]. In recent years, many studies have reported on the dynamic modeling [7][8][9][10], dynamic design [11][12][13][14], dynamic optimization [15][16][17][18][19][20], particle motion analysis [21][22][23][24], and spring failure diagnosis of vibrating screens [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The model validation was also carried out based on estimation of the riddle inclination angle ϕ s . According to Equation (9), which is linear with respect to l i and h i , the above-mentioned averaged acceleration is equivalent to acceleration measured in location as an average of all locations of sensors as follows: l a = 1/4 ∑ 4 j=1 l j = 0.051 m, h a = 1/4 ∑ 4 j=1 h j = 0.117 m. The ϕ s angle was evaluated based on displacement signals estimated for accelerometers located in the extreme positions in the front and rear parts of the screen riddle according to the following:…”
Section: Evaluation Of Parameters Of the Dynamic Screen Modelmentioning
confidence: 99%
“…In the industry, two main classes of screens are used: resonant type and above resonance type. Various constructions of vibrating screens and the tuning of their technological parameters are discussed in [7][8][9][10][11]. The resonance regime is desirable; however, its control is complicated due to vulnerability of the sieving process to changes in bulk material thickness, particle distribution over the deck and their physical properties [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…If high reliability of the mills, equipped with gear drives and involving open gears, is provided then they are quite cheaper than gearless ones [33], [34]. Increase in unit power of gear drives is to design mills where torque effect by motors (or a motor) is transmitted through a tooth rim with the help of several drive gears.…”
Section: Introductionmentioning
confidence: 99%